Visible Light Fence System for Indoor Kids Vehicles - Ibrahim, Nur Hafizah; Talib, Rahmat (Evolution in Electrical and Electronic Engineering, 2021)
Kid vehicle is available in the market with various shape and popular product for children. Equip this product with a playground area in a shopping mall is an important entity in business. Typical operation of kid vehicles in a shopping mall is based on manual handling and monitoring by human. In order to improve this operation, the virtual fence is proposed by providing an additional safety feature for the indoor playground. In this project, the virtual fence prototype was developed based on Visible Light Communication (VLC) technology by transmitting data between light from LED to photodetector or LDR module. Arduino modules were utilized in this prototype by integrating with several white LED and LDR module. On Off Keying (OOK) modulation technique was employed to transfer a code to kid vehicle. With this virtual fence, the boundary of the playground area can be set without a physical barrier. The developed prototype was successful to trigger the buzzer if the vehicle goes beyond the boundary.